Perspektif Kultural untuk Pengembangan Pengukuran Kebahagiaan Orang Jawa - Hanif Akhtar (Buletin Psikologi, 2018)
Studies on happiness are becoming popular. The present instruments, measuring happinessare mostly adapted from the Western perspective. Meanwhile, there are differences in themeaning of happiness in the context of Western culture (individualist) and Eastern culture(collectivist). An instrument measuring happiness that uses the perspective of Indonesiansociety has been developed. However, this scale is more likely measuring the cause ofhappiness, not happiness itself. The concept of happiness is still not clearly defined in the instrument. An in-depth study is needed to explore aspects of Javanese happiness as abasic reference for the development of the happiness scale. This paper has described theconcept of happiness according to Ki Ageng Suryamentaram and the difference with theWestern concept. Therefore, this article gives advice on developing a happiness scale that isaccurate by exploring the construct of happiness in the Java community